Gut microbiota and cardiovascular disease: exploring microbial metabolites, inflammation, and arterial specificity in atherosclerosis - Dicks, Leon Milner Theodore (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.